Ethanol extract of the mushroom Coprinus comatus exhibits antidiabetic and antioxidant activities in streptozotocin-induced diabetic rats - Nuniek Ina Ratnaningtyas; Hernayanti Hernayanti; Nuraeni Ekowati; Fajar Husen (Taylor & Francis Group, 2022)
Context Edible mushrooms have a long history of use in traditional Chinese or Japanese medicine. Coprinus comatus (O.F. Müll.) Pers. (Agaricaceae) contains antioxidant and antidiabetic agents.Objective To identify the benefits of ethanol extracts of the C. comatus fruit body in streptozotocin-induced hyperglycaemic rats by evaluating their blood glucose, glycosylated haemoglobin (HbA1c), insulin, glucagon-like peptide-1 (GLP-1), dipeptidyl peptidase-4 (DPP-4), and glutathione (GSH) levels, with and without extract administration.Materials and methods Wistar rats were either left untreated or were administered 45 mg/kg body weight (BW) streptozotocin; 45 mg/kg BW metformin; or 250, 500, or 750 mg/kg BW extract for 14 days. The blood glucose, GLP-1, DPP-4, GSH, insulin, and HbA1c levels were determined. Data were analysed using analysis of variance and Duncan's multiple range tests.Results Preliminary data showed that administration of C. comatus ethanol extract dose of 250, 500, and 750 mg orally has no toxicity effects after 24 h administration. The ethanolic extract of fruiting body of C. comatus considerably reduced the rat's fasting blood glucose levels 26.69%, and DPP-4 6.97% at dose of 750 mg. The extract reduced HbA1c 4-4.30%, increased GLP-1 71.09%, GSH 11.19% at dose of 500 mg, and increased insulin levels 13.83%. Extracts contain bioactive compounds such as flavonoid, alkaloid, terpenoids, vitamins C and E, rutin, and saponin.Conclusions The C. comatus extract can be used as herbal medicine that reduces diabetic symptoms. Further investigation on C. comatus extracts should be conducted with gas chromatography-mass spectrometry to characterise the bioactive compounds.